2018
DOI: 10.1186/s40792-018-0477-5
|View full text |Cite
|
Sign up to set email alerts
|

A rare mechanism of delayed splenic rupture following the nonoperative management of blunt splenic injury in a child

Abstract: BackgroundNonoperative management (NOM) has been established as the standard treatment for isolated blunt organ injury in hemodynamically stable pediatric patients. Although delayed splenic rupture or bleeding is a rare complication in NOM, it is an issue that many pediatric surgeons are greatly concerned about. We herein report a rare pediatric case concerning the mechanisms involved in delayed splenic rupture after NOM.Case presentationA 9-year-old boy with severe abdominal pain was transferred to our hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Etiologies may include subcapsular hematoma, pseudoaneurysm formation, splenic pseudocyst formation, or abscess formation. 3 Regardless of the cause, patients with splenic injury can have massive bleeding for greater than 24 hours after the initial trauma in up to 10 per cent of NOM of BSI, 1 but more commonly seen between 2 and 8 per cent of cases. 4 Up to 90 per cent of DSB occurs within 10 days of the injury, 1 with the vast majority of DSB occurring within 14 days of initial injury.…”
mentioning
confidence: 99%
“…Etiologies may include subcapsular hematoma, pseudoaneurysm formation, splenic pseudocyst formation, or abscess formation. 3 Regardless of the cause, patients with splenic injury can have massive bleeding for greater than 24 hours after the initial trauma in up to 10 per cent of NOM of BSI, 1 but more commonly seen between 2 and 8 per cent of cases. 4 Up to 90 per cent of DSB occurs within 10 days of the injury, 1 with the vast majority of DSB occurring within 14 days of initial injury.…”
mentioning
confidence: 99%
“…Interestingly, Shinkai et al, reported a case of a subcapsular tear during defecation, due to splenocolic ligament stretching. [3] Cases of splenic injury after colonoscopy, most often caused by traction on the splenocolic ligament or excessive manipulation during the procedure have been reported in the literature [4] Similarly, sneezing, coughing or the distention of the stomach after eating a heavy meal in a combination of rising of intra-abdominal pressure have also been associated with DSR [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is our firm belief that the management of atraumatic splenic rupture is basically the same as that for traumatic cases. If the vital signs are stable, preserved management may be an option [2] . In hemodynamically stable cases, interventional radiology can also be considered for control of bleeding [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Splenic rupture usually occurs secondary to blunt trauma, and its management is controversial. Non-operative management is recommended in hemodynamically stable patients but carries the risk of delayed splenic rupture [1] , [2] . In contrast, atraumatic splenic rupture is very rare and difficult to diagnose.…”
Section: Introductionmentioning
confidence: 99%